2018
DOI: 10.30659/nurscope.4.1.55-60
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Of Fatigue Post Stroke Patient’s

Abstract: Introduction: Fatigue in stroke patients can occur during the acute phase (2 weeks) or for a long time after the attack. This study aimed to find out the description of fatigue characteristics of post stroke patients. Descriptive analytical methodology with cross sectional design, 22 people (sample) obtained by purposive sampling technique. The research sample is stroke patient with fatigue. The results of the frequency distribution test showed the average age of respondents 54.68 ± 8.00 with 95% CI 48.90-61.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…This reflects that fatigue is very relevant to the decline in the motoric ability to carry out daily activities. In addition, several studies have also shown that women tend to experience fatigue faster than men (Noor, 2018). Where motor function in women also greatly affects the onset of fatigue in post-stroke patients.…”
Section: Post-stroke Patients Who Experience Fatiguementioning
confidence: 99%
“…This reflects that fatigue is very relevant to the decline in the motoric ability to carry out daily activities. In addition, several studies have also shown that women tend to experience fatigue faster than men (Noor, 2018). Where motor function in women also greatly affects the onset of fatigue in post-stroke patients.…”
Section: Post-stroke Patients Who Experience Fatiguementioning
confidence: 99%